Peranan Majelis Taklim Assalam Dalam Meningkatkan Pemahaman Agama Masyarakat Di Kecamatan Medan Helvetia Kota Medan - Nuraini Nuraini; Hadi Saputra Panggabean (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to determine the role played by Majelis Taklim Assalam in increasing religious understanding in the community of Medan Helvetia sub-district and to find out the supporting and inhibiting factors of Majelis Taklim Assalam in increasing the religious understanding of the community in Medan Helvetia sub-district. This research uses a qualitative approach because the data obtained is processed and explained in the author's description. In obtaining data, the author used observation, interview and documentation methods. Data analysis uses data reduction, data presentation, and conclusions. The results showed that the role of the taklim assembly in increasing religious understanding is as a place to gain knowledge and develop religious knowledge. Supporting factors for the Assalam taklim assembly include community participation, competent ustadz, adequate funding and availability of facilities. The inhibiting factors of the Assalam taklim assembly are the busyness of some worshipers, and internal conflicts.